Finding Zoe: A Deaf Woman's Story of Identity, Love, and Adoption - Rarus, Brandi; Harris, Gail (Writer on parenting), 1956- (Dallas, TX : BenBella Books, 2014)
"Four-month old Zoe was gradually losing her hearing. Her adoptive parents loved her-yet agonized- feeling they couldnt handle raising a deaf child. Would Zoe go back into the welfare system and spend her childhood hoping to find parents willing to adopt her? Or would Zoe be the long-sought answer to a mothers prayers? Brandi Rarus was just 6 when spinal meningitis took away her hearing. Because she spoke well and easily adjusted to lip reading, she was mainstreamed at school and socialized primarily in the hearing community. Brandi was a popular and happy teen, but communication-and being fully part of every conversation-was an ongoing struggle. In college, Brandi embraced Deaf Culture along with the joys of complete and effortless communication with her peers. For the first time, being deaf wasnt a handicap; it was a passport to a new and exciting world. Brandi went on to become Miss Deaf America in 1988 and served as a spokesperson for her community. It was during her tenure as Miss Deaf America that Brandi met Tim, a leader of the Gallaudet uprising in support of selecting the schools first deaf president. The two went on to marry and had three hearing boys-the first non-deaf children born in Tims family in 125 years. Brandi was incredibly grateful to have her happy and healthy family, but she couldnt shake the feeling that something was missing from her life. She had always dreamed she would have a daughter. Little did she know that just across the state line, Zoe was waiting for her. Set against the backdrop of Deaf America, Finding Zoe is an uplifting story of hope, adoption, and everyday miracles. "--
Keywords: Deaf women -- United States; Biography; Deaf children -- United States; Deafness -- United States; Adoption -- United States